2020
DOI: 10.1259/bjr.20201046
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of contrast-enhanced digital mammography in breast cancer detection in comparison to tomosynthesis, synthetic 2D mammography and tomosynthesis combined with ultrasound in women with dense breast

Abstract: Objective: To assess the diagnostic efficacy of contrast-enhanced digital mammography (CEDM) in breast cancer detection in comparison to synthetic two-dimensional mammography (s2D MG), digital breast tomosynthesis (DBT) alone and DBT supplemented with ultrasound examination in females with dense breast with histopathology as the gold-standard. Methods: It was a prospective study, where consecutive females presenting to symptomatic breast clinic between April 2019 and June 2020 were evaluated with DBT. Females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
18
2
Order By: Relevance
“…Our study showed that accuracy for DBT, DBT + USG and MRI were 79.1%, 83.3% and 79.1%, respectively. This was in accordance with a study done by Sudhir et al, whose study showed similar accuracy of 83.7% for DBT and 84.3% for DBT + USG; however, it was not statistically significant [ 24 ]. Saxena et al, on the other hand reported better accuracy for DBT and MRI, which were 90% and 98%, respectively [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study showed that accuracy for DBT, DBT + USG and MRI were 79.1%, 83.3% and 79.1%, respectively. This was in accordance with a study done by Sudhir et al, whose study showed similar accuracy of 83.7% for DBT and 84.3% for DBT + USG; however, it was not statistically significant [ 24 ]. Saxena et al, on the other hand reported better accuracy for DBT and MRI, which were 90% and 98%, respectively [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…NPV values in our study for all three modalities were less variable compared to other studies, which were 91.6%, 92.3% and 100% versus 81.7–100%, 86.3% and 89.5–100% for DBT, DBT + USG and MRI, respectively [ 8 , 10 , 24 ].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The highest diagnostic performance is achieved when interpretation includes both low-energy and recombined images and jointly consider lesion morphologic characteristics and contrast enhancement [3]. Important is the high performance in women with dense breasts, and CEM was shown to have higher sensitivity and negative predictive value in females with dense breasts compared to DBT alone or DBT combined with ultrasound [4].…”
mentioning
confidence: 99%